Cryoprotectant effects of mangiferin on the quality of frozen-thawed boar sperm - Zhang, Minhao; Luo, Zhaobo; Mao, Weipu; Zhang, Guangyuan; Gu, Peng (Frontiers in Veterinary Science, 2026)
Boar sperm is particularly vulnerable to damage at low temperatures, leading to reduced efficiency in cryopreservation. This study aimed to analyze the effect of mangiferin (Man) on boar sperm cryopreservation efficiency. Various concentrations of Man (0, 5, 10, 20, and 40 μM) were added into the cryopreservation extender and analyzed for their effects on sperm motility, kinetic parameters, acrosome integrity, plasma membrane integrity, DNA integrity, mitochondrial membrane potential, total antioxidant capacity (T-AOC) levels, hydrogen peroxide (H2O2) content, glutathione (GSH) levels, malondialdehyde (MDA) levels, and reactive oxygen species (ROS) levels. The results indicate that, in comparison to the control group, 10 μM Man significantly enhances sperm total motility, progressive motility, average path velocity, average straight-line velocity, average curvilinear velocity, and beat frequency during the cryopreservation of boar semen. Furthermore, our studies demonstrated that 10 μM Man significantly enhance mitochondrial membrane potential, acrosome integrity, plasma membrane integrity, and DNA integrity in boar sperm after thawing. Additionally, treatment with 10 μM Man markedly increase GSH levels and T-AOC in boar sperm, while simultaneously reducing MDA, H2O2, and ROS levels. Consequently, the findings of this study suggest that treatment with 10 μM Man substantially improve the efficiency of boar semen cryopreservation.